Reaksi Pasar Modal Terhadap Dibatalkanya Indonesia Sebagai Tuan Rumah Piala Dunia U20 Tahun 2023 (Studi Pada Perusahaan Yang Terdaftar Pada Index IDX30) - Pramanaswari, A.A Sagung Istri; Mertaningrum, Ni Luh Putu Erma (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2023)
This study aims to determine the reaction of the capital market, which is indicated by differences in abnormal returns and trading volume activity in companies indexed IDX30, due to the announcement of the cancellation of Indonesia as host for the 2023 U-20 World Cup. This research uses the event study method with an approach quantitative. Through the one sample t-test, it is known that the significance value of the average abnormal return before and after the event is 0.126, while the value of the average trading volume activity before and after the event is 0.723 which is greater than 0.05. So the results of this study explain that, the event of Indonesia's cancellation as the host of the U20 world cup in 2023, did not have an impact on the capital market, this was because there were no changes in the average abnormal return and average trading volume activity, in IDX30 indexed companies.